Coupled inter-site reaction and diffusion: Rapid dehydrogenation of silicon vacancies in natural olivine. (1st October 2019) - Jollands, Michael C.; Kempf, Elias; Hermann, Jörg; Müntener, Othmar
Abstract: Natural olivine from Zermatt (Switzerland) and Almklovdalen (Norway) were dehydrogenated at 1 bar, 517–1009 °C at various oxygen fugacity conditions. Following experiments, H contents (either bulk, or core-rim profiles) were measured using Fourier transform infrared spectroscopy, and spectra were resolved into Gaussian peaks. The starting olivine contained ∼150 and ∼10 wt. ppm H2 O for the Zermatt and Almklovdalen samples respectively, but importantly the initial H distribution in both corresponded to defects with 4H + occupying Si vacancies. Experiments in pure forsteritePadrón-Navarta and Hermann, (2017) showed that this defect diffuses very slowly relative to other H diffusion mechanisms in olivine. Conversely, we show that, in the Almklovdalen samples, H loss from the Si-vacancy defect can be extremely rapid, and approaches the fastest known mechanism of H diffusion (proton-polaron diffusion) in olivine. The rate of dehydrogenation from the Zermatt olivine is slightly slower, more consistent with the diffusivity of hydrogenated M-site vacancies. The sum of all defects, along with the integrated area of the main Si vacancy peak (3612 cm −1 ) generally shows simple diffusive behaviour, whereas profiles (or maps) resolved into individual peaks reveal complex profile shapes not consistent with a simple out-diffusion mechanism. This behaviour can be modeled as a combination of inter-site reaction and diffusion, whereby H leaves the tetrahedral site, moves into a faster diffusion pathway, then rapidly exits the crystal. The rate of H loss from, or gain into, olivine can therefore be either diffusion limited, reaction limited, or a combination of the two. This may explain current discrepancies between experiments conducted under different conditions and between experimental and natural data, including the recent observation that H stored in Si vacancies in metamorphic olivine may be retentive over millions of years, despite the capability to diffuse rapidly via a different mechanism.